Design of Employee Absence System Using Web-Based Realtime Geo-Location Library - Nur Azizah Yusuf; Muhammad Muhaimin Nur; Andi Hutami Endang (Program Studi Teknik Komputer, 2025)
Employee performance is one of the most critical aspects of a company or organization. This is because the company's goals or targets can only be achieved if employees can demonstrate good performance in achieving them. One way to ensure this is by maintaining employee discipline. This study proposes a web-based employee attendance system using the Geo-Location Realtime library to monitor employee discipline at PT. Portal Indonesia Perkasa, which previously relied solely on a fingerprint-based attendance system. The method used is the waterfall method. Which employs a systematic and sequential approach. The system design includes flowcharts, use case diagrams, data flow diagrams, and logical legal structures. The main features include real-time location tracking and automatic attendance recording. Implementation results show the system's effectiveness in facilitating accurate attendance monitoring and reporting.